Characterization of Salt Quality from Artemia (Artemia franciscana) Cultured Water with Dunaliella salina as Natural Feed - Himna Sayyyidatul Islamiyah; Mochammad Amin Alamsjah; Laksmi Sulmartiwi (Department of Aquaculture, 2022)
The high demand for domestic salt cannot be achieved by local salt production from traditional salt and PT. Garam fluctuates every year. In addition, the quality of traditional salt is still low. This causes the need for domestic salt consumption to be met by imported salt. Therefore, it is necessary to have an alternative to meet the domestic salt demand, namely the revitalization of salt ponds for the development of mass Artemia cultivation that produces both Artemia production and biomass and produces salt in one location. In its natural habitat, Artemia uses microalgae as its main food source. The quality of microalgae feeds greatly determines the production of Artemia franciscana. The availability of nutrients is a factor that determines the rate of growth, so the amount and quality of feed are the main factors to meet the nutritional content for optimal development. Therefore, the salt production in this study used saltwater cultured Artemia with Dunaliella salina as a natural feed with a water age of 3rd,7th, and 14th days. This study aimed to determine the best age of Artemia water cultured with Dunaliella salina as a natural feed in salt production. The results showed that the different ages in Artemia water cultured with Dunaliella salina had a significant effect (p < 0.05) on salt characteristics. The best result was D7 which is salt from Artemia cultured water with Dunaliella salina as a natural feed with water age 7th day. Their respective values are 0.66a + 0.33 water content, 91.55 + 0.32 NaCl, 0.87 water-insoluble part, 0.39% + 0.01 Ca, and 1.25a + 0.05 Mg.